Application of crowd simulation for modelling infectious disease spreading - Xing, Wanting (Nanyang Technological University, 2021)
Crowd simulation has been a widely applied to study the movement and/or behaviour of a large number of crowds. In recent years, it has been widely applied to various fields of research, such as entertainment, traffic engineering and city planning. Under the current situation of COVID-19 pandemic, crowd simulation is an effective approach for studying the spread of infectious disease among populations.